Prevalence of and risk factors associated with HIV, Herpes Simplex Virus-type 2, Chlamydia trachomatis and Neisseria gonorrhoeae infections among 18-24 year old students attending Higher Learning Institutions in Mbeya-Tanzania. - Ruby Doryn Mcharo; Abisai Kisinda; Lilian Njovu; Miri Mcharo; Florida Mbwilo; Getrude Mihale; Beatrice Komba; Ernest Andrew; Philippe Mayaud; Arne Kroidl; Olena Ivanova; Sia Emmanueli Msuya (PLoS ONE)
Background Sexually transmitted infections (STIs) are common among young people in low- and middle-income countries and are associated with negative reproductive and pregnancy outcomes. Most of the studies have assessed HIV among adolescents and young adults, with limited information on occurrence of other STIs in this population. This study aimed to describe the prevalence of and risk factors associated with Herpes Simplex Virus-type 2 (HSV-2), Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Syphilis and HIV infection among young adults attending Higher Learning Institutions (HLIs) in Mbeya, Tanzania. Methods We conducted a cross-sectional study among students aged 18-24years attending HLIs in Mbeya-Tanzania, randomly selected using a computerized random number. Participants were tested for HSV-2, CT, NG, Syphilis and HIV infection. We used a self-administered questionnaire to collect information on sexual activity and risk factors to the tested STIs. Results We enrolled 504 students from 5 HLIs, with mean age of 21.5 years (SD 1.7). 17% of the students had at least one STI; prevalence was higher among females than males (21.1% versus 14.1%). CT (11%) and HSV-2 (6.1%) were the most common STIs, while NG (1.1%) and HIV (0.7%) infection had the least occurrence. None of the participants was diagnosed with Syphilis. In univariate analysis, predictors for STIs were Sex, inconsistent condom use in the past 4weeks, report of oral sex, sexual orientation (bisexual/homosexual) and having a sexual partner with an age-difference of at least 5years (either older or younger); while in the multivariate analysis, Sex, inconsistent condom use in the past 4weeks and sexual orientation (bisexual/homosexual) remained significant. Conclusion STIs such as Chlamydia and HSV-2 which are commonly asymptomatic are of concern among young adults attending HLIs. The latter is an important group that needs attention and recognition that is pivotal in transmission of STIs considering their risk. Information, Education and Communication (IEC) campaigns targeting young adults, especially those at HLIs, need to focus on exposure-risk minimization. Funding institutions that have invested heavily on HIV prevention campaigns should consider giving similar recognition to other STIs for a streamlined outcome.